Congenital X‐Linked Retinoschisis: An Updated Clinical Review. Issue 3 (May 2018) - Rao, Prethy; Dedania, Vaidehi S.; Drenser, Kimberly A.
Abstract : Abstract: : We present an updated clinical review of the pathophysiology, progression, and current treatments in pediatric patients with congenital X‐linked retinoschisis (CXLRS). CXLRS is an X‐linked inherited retinal degeneration characterized by splitting of the superficial layers of the retina. Most recent classification divides CXLRS into 4 distinct clinical phenotypes: type 1, foveal; type 2, foveolamellar; type 3, complex; and type 4, foveoperipheral. The majority of retinoschisis cavities remain stable throughout life and may spontaneously collapse. However, a select number of patients progress to macula‐involving peripheral retinoschisis, rhegmatogenous, and combined tractional‐rhegmatogenous detachments that require further intervention. Although several advances have been made over the past several decades, medical therapy remains limited to case series‐based carbonic anhydrase therapy and prophylactic laser retinopexy. Recent advances in genetic‐based clinical trials with the retinoschisis gene are promising. Vitreoretinal surgical approaches remain complex, case‐based, and require careful planning depending on the configuration and location of the retinoschisis cavity.